THE AIM OF POLITICAL SYSTEM IN AFRICA - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
A growing trend in contemporary development research is to define development not only in economic terms but also as freedoms and capacities that individuals have to improve their social and economic standing (Pereira and Teles, 2010). While economic growth is crucial to sustained poverty reduction, institutional and social changes are also essential to the development processes and the inclusion of poor people (World Bank 2012). At the same time, themes of political stability and corruption have called for an analysis of global and national political structures and of their impact on socio-economic relationships(Acemoglu, 2012).